2010
DOI: 10.1016/j.physc.2010.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Doping dependence of Meissner effect in cuprate superconductors

Abstract: Within the t-t'-J model, the doping dependence of the Meissner effect in cuprate superconductors is studied based on the kinetic energy driven superconducting mechanism. Following the linear response theory, it is shown that the electromagnetic response consists of two parts, the diamagnetic current and the paramagnetic current, which exactly cancels the diamagnetic term in the normal state, and then the Meissner effect is obtained for all the temperature $T\leq T_{c}$ throughout the superconducting dome. By c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(76 citation statements)
references
References 56 publications
(125 reference statements)
5
71
0
Order By: Relevance
“…In this case, we have fitted the relation between T c and ρ s in the underdoped regime, and the result shows that triangular-lattice superconductors satisfy the similar Uemura relation in the underdoped regime 26,27 . Incorporating the result obtained from square-lattice cuprate superconductors 23 , it thus implies that the Uemura relation may be a universal relation in strongly correlated superconductors in despite of whether the gap nodes at the charge-carrier Fermi surface exist or not.…”
Section: Doping Dependence Of Electromagnetic Responsementioning
confidence: 93%
See 4 more Smart Citations
“…In this case, we have fitted the relation between T c and ρ s in the underdoped regime, and the result shows that triangular-lattice superconductors satisfy the similar Uemura relation in the underdoped regime 26,27 . Incorporating the result obtained from square-lattice cuprate superconductors 23 , it thus implies that the Uemura relation may be a universal relation in strongly correlated superconductors in despite of whether the gap nodes at the charge-carrier Fermi surface exist or not.…”
Section: Doping Dependence Of Electromagnetic Responsementioning
confidence: 93%
“…As in the case of square-lattice superconductors 23 , the second term in the right-hand side refer to the contribution from the electron spin, and can be shown that…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations